SOCIAL INSURANCE AS A TOOL FOR REDUCING OCCUPATIONAL INJURIES IN THE AGRICULTURAL SECTOR OF UKRAINE - Саламаха, Ірина; Гордійчук, Лариса (SWorldJournal, 2025)
The article examines the system of social insurance against occupational accidents as a key tool for reducing workplace injuries in the agricultural sector of Ukraine. It explores the legal, economic, and organizational foundations of this system and defi